ECONOMIE DE ECHILIBRU, REZILIENȚĂ ȘI GLOBALIZARE - Stoenescu, Constantin (CEP USM, 2024)
The idea of a steady state economy can still be found in Adam Smith works, but its explicit formulation as an interdisciplinary concept between economics and ecology is late and belongs to Herman Daly. He defines his concept as an economic system made up of a constant stock of capital and a constant stock of population, both maintained by a constant flow of natural resources. Apparently such a system is resilient, but challenges arise if we consider the current trends of a globalised society. My aim is to offer a theoretical reconstruction of the concept by related it with contemporary development in philosophy, economics and social theory. Moreover, I bring up to date the conceptual system developed by Nicholas Georgescu-Roegen in his The Entropy Law and the Economic Process, so that to rethink Daly’s project in a transformational manner according to the concept of sustainable development.
BALANCE ECONOMY, RESILIENCE AND GLOBALIZATION
Keywords: Equilibrium economy; globalization; Herman Daly; resilience; Nicholas Georgescu Roegen; Economie de echilibru; globalizare; reziliență; Nicholas Georgescu Roegen